Workload Analysis In Family Street Stall Business Operations - Dhea Rengganing Tyas; Silviana Kusuma Dewi; Honorata Ratnawati Dwi Putranti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to analyze the workload faced in the operations of Pak Haji Edy's Tahu Gimbal family business. This family business is an example of micro-entrepreneurship in the culinary industry and is essential in the regional economy. This research focuses on an in-depth understanding of how workload affects business continuity and the quality of life of these families. The research methodology requires implementing a case study using a qualitative approach. Information was gathered through extensive interviews with Mr. Haji Edy and his family members, direct observation of business operations, and analysis of related documents. The research results revealed that Pak Haji Edy's Tofu Gimbal business faced a reasonably high workload. This workload includes operational aspects, marketing, business management, and social roles in the family. This business positively impacts the household budget, but hard work also affects the family's standard of living and overall health. Analysis of workload in the operations of the Tahu Gimbal Pak Haji Edy family business shows the need for support in the form of training, better time management, and strengthening social capital. This initiative helps improve the quality of life for these families and supports the development of small businesses in the community. This investigation further provides significant insight into the complex barriers small businesses face in the local economy face.